Comparison of different tracheal intubation methods for unstable upper cervical spine injuries in a human cadaver model - Uzun, Davut D.; Schneider, Niko; Liao, Shiyao; Schmitt, Felix; Weigand, Markus A.; Kreinest, Michael; Popp, Erik; Weilbacher, Frank (Scientific reports, 2025)
In severe trauma, it is estimated that approximately 2% of patients will sustain a spinal cord injury. The optimal method for advanced airway management that will minimize any associated cervical spine movement remains a topic of debate. Therefore, the aim of this study is to compare the effects of different tracheal intubation techniques in unstable injuries of the cervical spine. Tracheal intubation using conventional laryngoscopy (CL), video laryngoscopy (VL) or flexible bronchoscopic intubation (FO) was performed in six fresh human cadavers. Compression of the dural sac as well as angulation, distraction and intubation time were assessed by myelography in the presence of isolated atlantooccipital dislocation (AOD) and of combined atlanto-occipital dislocation with atlanto-axial instability (AAI). In case of an isolated AOD, FO intubation resulted in significantly less compression of the dural sac at both levels compared to CL (− 0.46 mm vs. − 1.31 mm; p < 0.001, r = .66) for C0/C1 and (− 0.09 mm vs. − 0.19 mm; p = < 0.05, r = .36) for C1/C2 and VL (− 0.46 mm vs. − 0.64 mm; p = < 0.05, r = .42 for C0/C1 and (− 0.09 mm vs. − 0.22 mm; p = < 0.01, r = .52) for C1/C2. Atlanto-axial Angulation in simultaneous AOD and AAI, the differences between CL and VL were significantly in favor of VL (4.1° vs. 3.2°; p = < 0.05, r = .39), and using FO resulted in less angulation than CL (2.5° vs. 4.1°; p = < 0.001, r = .60) and VL (2.5° vs. 3.2°; p = < 0.05). FO required longer in the case of combined AOD and AAI (FO 16.6 s vs. CL 9.8 s; p = < 0.001, r = .56), (FO 16.6 s vs. VL 9.7 s; p = < 0.001, r = .56). The study demonstrated that tracheal intubation using VL caused significant less compression of the dural sac than the CL. FO showed the lowest compression at all measuring points, but took almost twice as long. For elective or stable patients, where time to airway management is not a relevant factor, FO appears to be the safest method. However, FO is not available everywhere, and in urgent emergency situations, the longer duration may not be acceptable. In such cases, video laryngoscopy can represent a compromise between duration and patient safety, and most physicians have more clinical experience with VL than with FO.
Gesehen am 02.12.2025